ERGONOMICS MEASUREMENT TOOL: A SURVEY FROM PUBLIC SECTORS EMPLOYEES - Abdullah, Nor Azimah Chew (CENTRAL ASIA AND THE CAUCASUS, 2024)
Ergonomic is a branch of science that focuses on the design of task or job, work equipment and work space and adapts the job and/or the equipment to fit the worker. The suitability of work equipment and work space with employees by considering also the capabilities with the limitations of the employees to ensure the fitness achieved. This design process takes into account the ability of human physiology and psychology. Thus, the aim of the survey was to validate the ergonomic checklist to develop ergonomic measurement scale to measure relationship with employees’ perception on ergonomics problem at the workplace influence employees’ body discomfort. 184 employees from the public sector were selected to participate as respondents. Results showed that this study has confirmed the acceptable internal consistency of the constructs demonstrated. The validity in assessing the measurement was confirmed by the instrument. Further work is needed to investigate the dimension of ergonomic risk factors to ensure that the instrument has valid outcome measures.